Road and Belt, Iron Silk Road and Russian-Chinese geopolitical cooperation and competition - Artyom Lukin (OrdnungsPolitisches Portal (OPO), 2021)
This paper examines political and economic dimensions of the Russia-China relationship, with an emphasis on Russia's involvement in Beijing's Belt and Road Initiative (BRI). Being the largest, and trans-continental, Eurasian country, Russia occupies an important place in China's BRI. The current relationship between the two great Eurasian powers can be characterized as an entente, or quasi-alliance. Moscow welcomes the BRI, but, unlike many other governments across the world, it has never signed an agreement to formally join the initiative. This signals Russia's stance that Eurasian integration should not be dominated by China, as well as the Kremlin's insistence on status equality with China. In recent years there has been a noticeable rise in shipments from China to Europe, and in the reverse direction, using the rail routes via Russia. However, despite the increase in its trans-continental freight traffic going via Russia, China still refrains from investing in the upgrade of Russia's transport networks, such as railroads, ports and highways, and is overall reluctant to invest in the Russian economy. The reasons are both economic, such as the relatively high risks and low profit margins in the Russian market, and political ones, related to Russia's insistence on parity and equality with China.
Keywords: 330; Russia-China relations; the Belt and Road Initiative; Eurasia